Diagnostic value of the JAK2 V617F mutation for latent chronic myeloproliferative disorders in patients with budd-chiari syndrome and/or portal vein thrombosis - Karaköse, Süleyman; Oruç, Nevin; Zengin, Melia; Akarca, Ulus Salih; Ersöz, Galip (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: The diagnosis of an underlying myeloproliferative neoplasm (MPN) is often problematic in patients with Budd Chiari syndrome (BCS) or portal vein thrombosis (PVT). This study aimed to assess the diagnostic value of the JAK2 gene V617F gain-of-function mutation for MPN in splanchnic vein thrombosis patients. Materials and Methods: One hundred eleven patients (80 with PVT, 27 with BCS, and 4 with BCS and PVT) were investigated. The control group included 56 volunteers without any known diseases. LightCycler SNP genotyping was performed to detect the JAK2 V617F mutation in DNA extracted from peripheral blood. Results: The JAK2 V617F mutation was identified in six of 28 patients (21.4%) with idiopathic PVT or BCS and in eight of 45 patients (17.8%) with PVT or BCS secondary to a known prothrombotic factor, but in only one of 38 patients (2.6%) with PVT and cirrhosis (p=0.049). Conclusion: The JAK2 V617F mutation is a noninvasive molecular marker for occult MPNs and can be used for the diagnosis of latent MPNs presenting with thrombotic events. Analysis of JAK2 mutation in the patients with idiopathic PVT or BCS showed that 20% had latent MPNs. In addition to this JAK2 mutation, prothrombotic events were observed in a significant number of patients with splanchnic vein thrombosis. JAK2 gene analysis should be included in the research panel for BCS and PVT patients without cirrhosis.